The Correlation of Financial Management Practices and Controlling Mechanisms for Financial Management Challenges and Issues The Case of Franciscan Missionaries of Mary Congregation - War War; Maria Joan P. Barlis (Bina Nusantara University, 2023)
The study analyzed financial management practices and controlling mechanisms for financial management challenges and issues in religious congregations, specifically the Franciscan Missionaries of Mary Congregation. The study was based on a questionnaire survey sent to 305 respondents among the religious sisters. Weighted mean and the Spearman rho coefficient values were applied in the statistical processing of the data. The results showed a significant positive relationship between financial management practices and the controlling mechanisms for financial management challenges and issues, suggesting that a lack of control mechanisms could lead to the possibility of fraud. The study suggests that good financial management practices impact management resources and decision-making. The study highlights the importance of financial management practices for non-profit organizations, as they can be prone to financial challenges and issues due to lack of resources or mismanagement and its effectiveness is crucial for the sustainability, growth, and impact of the organization.